An appraisal of leadership role conception and Nigeria’s foreign policy at the regional level (2018)
This paper examines leadership role conception within the context of Nigeria 's foreign policy at the regional level. The nature and scope as well as the rational basis of Nigeria 's leadership role in Africa are examined. It argues that leadership role is not only an aspect of Nigeria's dignity as the most populous country in Africa but is also crucial to no{e that there was a tacit international recognition that Nigeria is destined to play a leading role in African affairs. Thus, international legitimacy of Nigeria through independence in 1960 gave the country the responsibility of playing an active role in African affairs. Central to this discourse are: the psychological reasons why Nigeria is supreme in Africa, factors that influence Nigeria 's leadership role in Africa, including the interrogation of selected foreign policies within the context of Nigerian-African diplomacy. Since 1970s, Nigeria's leadership role in regional affairs has been very visible and commendable. However, Nigeria's diplomatic influence in Africa declined in the 1990s as a result of domestic political and economic crisis. In spite of these challenges, no external policy issues has preoccupied Nigeria more than Nigerian African diplomacy. The paper concludes by asserting the need for Nigeria to stabilize its domestic polity in order to continue playing a leading role in regional affairs.